Jim Butcher's The Dresden files. Fool moon, Volume one - Butcher, Jim, 1971- (Butcher, Jim, 1971- Dresden files., 2011)
"Harry Dresden's life is a mess. His top client (and close friend), Lt. Karrin Murphy, no longer trusts him. Chicago's underworld and the cops alike think he's mobster Johnny Marcone's supernatural enforcer. And the enigmatic White Council continues to view him with suspicion. If all that weren't enough, a pack of werewolves have unleashed a wave of terror on the Windy City. But as is always the case when it comes to the creatures of the Nevernever, there's far more going on than meets the eye."--Amazon.com.